Southern Tagalog society in a time of transition, 1571-1671 - De Castro, Maria Eloisa P. (2010)
This paper looks into the transformation of the village communities in the Southern Tagalog provinces of Cavite, Batangas and Laguna at the point of contact with the Spaniards beginning in 1570. Based on a careful reading and critical reading/re-reading of some of the earliest historical writings by the Spanish civil authorities and friar missionaries, as well as available manuscripts on the establishment of towns and provinces, the paper reconstructs the nature of the leadership that confronted the Spanish conquest and the changes brought about by pacification and resettlement in the reducción. The geographic proximity to the newly-designated capital of Manila and the distinct topographical features of these three Southern Tagalog provinces were probably significant for the development of a new social structure of leadership in these provinces. The close links of their coastal areas along Laguna de Bay to Manila Bay for commerce and defense, and the cultivation of certain products in their lowland and upland regions, are among the factors that shaped (1) the relationship between the Spanish colonizers and the indigenous communities and their leaders; (2) the system of property ownership (specifically land) in the area; and (3) its access to foreign trade.
Keywords: Southern Tagalog -- Social aspect; Philippines -- History -- 1521-1812